The answer is 8.35. Have a nice day hope this helped!
Answer:
I believe your answer would be 8 dollars and 75 cents. I don't know for sure.
Step-by-step explanation:
Answer: .1<u>6</u> Well, we can just call this a simple negative two divided by three plus 5 divided by 6. Using the *cough order of *cough *cough operations, or GEMA, we can see that we can separate this expression into two.
-2/3+5/6
(-2/3) + (5/6)
By simplifying each side of the expression, we will receive:
-.<u>6</u> + .8<u>3</u> ["Negative point six repeating plus point 8, 3 repeating"]
This adds up to .1<u>6</u>, or point 1, six repeating.
Answer:
x = -2.38
Step-by-step explanation:
divide 3 to up 3x then 4 and divide them by 2.
Answer:
see explanation
Step-by-step explanation:
(A) Given
4(2x - 3) = 4 ( divide both sides by 4 )
2x - 3 = 1 ( add 3 to both sides )
2x = 4 ( divide both sides by 2 )
x = 2
(B)
As a check substitute x = 2 into the left side of the equation and if equal to the right side then it is the solution.
4(2(2) - 3) = 4(4 - 3) = 4(1) = 4 = right side
Hence x = 2 is the solution